Nilai Tambah Pengolahan Dan Efesiensi Saluran Pemasaran Bubuk Kopi Arabika (Coffea Arabica L.) Studi Kasus Sam’s Coffee Di Kabupaten Solok - Fauzi, Dian; Nurhasanah, Dwi; Dermawan, Alvindo (MAHATANI: Jurnal Agribisnis (Agribusiness and Agricultural Economics Journal), 2025)
Sam's Coffee is one of the small and medium industries (IKM) engaged in processing Arabica coffee into coffee powder. This study aims to analyze the income of processed coffee powder products, the added value generated from the processing process, marketing channels, and marketing efficiency applied by Sam's Coffee. Uses a purposive case study method at Sam's Coffee. The data used consists of primary and secondary data. Data analysis was carried out descriptively-qualitatively and quantitatively, with an income and profit analysis approach, added value analysis using the Hayami method, and channel analysis and marketing efficiency. The results of the study showed that in each production cycle, Sam's Coffee earned an income of IDR 488,650.25 with a net profit of IDR 402,167.66. Although the profits obtained are not too large, this business is still profitable and has the potential to develop further through more optimal production cost efficiency and marketing strategies. The process of processing red cherries into coffee powder produces a value-added ratio of 1,.56 percent, indicating a positive contribution from processing to increasing the value of the final product. In terms of marketing, Sam's Coffee uses a zero-level marketing channel, where products are sold directly to consumers through outlets and digital platforms. Marketing is also strengthened by participation in events and bazaars to expand the market network. Marketing efficiency analysis shows very high efficiency with a value of 0.97 percent, indicating that the marketing costs incurred are relatively low, thus providing good price competitiveness in the market.